Aktivitas Antimikroba Minuman Probiotik Sari Jambu Biji Merah (Psidium guajava L.) Terhadap Escherichia coli dan Shigella dysenteriae - Mira Andam Dewi (Universitas Bhakti Kencana, 2015)
Probiotics are live microorganisms when consumed in sufficient quantities to provide health benefits to host. Red guava (Psidium guajava L) is one of the many types of fruit are produced in Indonesia, which contains fructose and glucose monosacaride be high enough. The aims of this research was to evaluate the antimicrobial activity of probiotic drink red guava juice for digestive tract bacteria is Escherichia coli and Shigella dysenteriae. Research methods include phytochemical screening, the manufacture of probiotic drinks, quality testing and test activities. Results of phytochemical screening red guava fruit showed flavonoids, tannins and polyphenols. Probiotic drinks made into 2 formulas. The first formula without the addition of skim milk and the second formula with the addition of skim milk concentration of 7.5%. Both use a combination of Lactobacillus bulgaricus and Streptococcus thermophilus (1: 1). Tests include organoleptic quality probiotic drink (shape, color, aroma, flavor), and the pH value of qualitative and quantitative tests lactic acid. The test results showed levels of lactic acid and pH value for first formula and second formula in a row is 1.65%; 1.98%; 4.98; 4.20. Testing the activity of probiotic drinks using Total Plate Count method. The first formula resulted a reduction of Escherichia coli populations by 7.55% at 0 hours and 26.61% at 72 hours, Shigella dysenteriae 8.26% at 0 hours and 28.34% at 72 hours. On the second formula resulted a reduction of Escherichia coli population of 10.43% at 0 hours and 31.65% at 72 hours, Shigella dysenteriae 11.41% at 0 hours and 35.43% at 72 hours. The second formula is the best formula in reducing two test bacterial population on dilution 107 cfu / mL.